2002
DOI: 10.1039/b205220m
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method of synthesizing the layered titanosilicate JDF-L1

Abstract: A rapid procedure for synthesis of highly crystalline and pure samples of JDF-L1 without using organics are reactants or templates is described and indexation of the powder X-ray diffraction pattern of this phase is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
4
17
0
Order By: Relevance
“…The chemical compositions of Na + -titanosilicate and H + -titanosilicate are shown in Table 1. By combining Na2O, SiO2, TiO2 and weight loss, we obtained an empirical composition for synthetic Na + -titanosilicate of Na4Ti2Si8O22·4H2O, which compares well with those reported previously [3][4][5][6]. H + -titanosilicate, as shown in Fig.…”
Section: Synthesis Of Na + -Titanosilicate and H + -Titanosilicatesupporting
confidence: 70%
See 1 more Smart Citation
“…The chemical compositions of Na + -titanosilicate and H + -titanosilicate are shown in Table 1. By combining Na2O, SiO2, TiO2 and weight loss, we obtained an empirical composition for synthetic Na + -titanosilicate of Na4Ti2Si8O22·4H2O, which compares well with those reported previously [3][4][5][6]. H + -titanosilicate, as shown in Fig.…”
Section: Synthesis Of Na + -Titanosilicate and H + -Titanosilicatesupporting
confidence: 70%
“…Kostov-kytin and co-workers [6] also investigated on the phase transition of Na + -titanosilicate during heating at 300-700 o C. However, studies of Na + -titanosilicate are still in the early stage. For industrial applications, in which Na + -titanosilicate is used as a catalytic support, studies on surface chemistry, surface area, and porosity are needed, and on the relations between its surface properties and basic intercalation chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Since their introduction in 1983, various categories, such as microporous [6][7][8], mesoporous [9][10][11][12][13] and layered types [14][15][16][17][18][19], have been synthesized. These target different applications, such as ion exchange [20][21][22][23][24], adsorption [25][26][27][28], membrane separation [29][30][31][32], pillaring templating [33,34] and oxidation catalysis [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a general synthetic strategy was developed during the studies of JDF-L1 (Na 4 Ti 2 Si 8 O 22 Á4H 2 O) by Robert et al [21]. Ferdov et al also reported a convenient preparation of JDF-L1 [22], which contains Na ? -JDF-L1 layers composed of tetrahedral SiO 4 units and square pyramidal TiO 5 polyhedrons [21].…”
Section: Introductionmentioning
confidence: 99%
“…-JDF-L1 [21]. The titanium in JDF-L1 is five-coordinate and has excellent catalytic ability for oxidation reactions [22]. Each layer is separated by water molecules around an interlayer of Na ?…”
Section: Introductionmentioning
confidence: 99%